Discourse Analysis : Temple will be Forsake Feudalism will be Proud Arrogant - Sutheeworasarn, Phrakru; Payoko, Phamaha Jirayuth (Journal of Graduate MCU KhonKaen Campus, 2022)
One of the current problems of the sangha is that religious heirs are much less ordained. In some provinces that used to have a lot of monks, there are only a few monk left. The more cute little novices some temples are barely visible. The cubicle has only an empty room. most of them all flow into the city. some of the temples are the temples of the district primate level. there are less than 10 monks because at present there are fewer monks to learn. an important external problem is the inadequacy of the situation of the sangha act. disciplinary punishment, against monks who acted outside discipline, including dealing with those who seek the benefits of religion. the very important internal problems are self-protection, precepts, discipline, and ecclesiasticalunity. Management of sangha affairs in the information technology era it is the most important thing to preserve the dharma, discipline, and the sangha to be sustainable. But the current situation reflects some behaviors that are not suitable for priest, destroying religion, such as excessive media use, lay-like lifestyle habits such as self-driving by claiming that the discipline does not forbid and himself. having a driving license (before ordination) is not illegal. the use of monk language that is woe along with the behaviors expressed today. If the clergy and the elders have positions Ecclesiastical administration and the monk-novice itself is still indifferent or neglect to use the haphazard regime. including the administration of the national buddhism office, etc. The future of buddhism will be dwindling and may be swallowed up by other religions and cultures. the answer to the future of buddhism can be found in the minds of the four assemblies of buddhists